PENGARUH KONFLIK KELUARGA DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR IPS KELAS V MIN SAMARINDA, KALIANTAN TIMUR - Zaenab Hanim; Siti Aisyah; Yudo Dwiyono; Bahrani Bahrani (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
This study aims to determine the effect of: 1) Family Conflicts on Student Results IPS class V. 2) Learning Motivation on the results of Student IPS Study of class V. 3) Family Conflicts and Motivation Learning together to Class IPS Student Learning Outcomes V. This research was conducted in State Islamic Primary School I Samarinda. The method used correlation with quantitative approach that is multiple influence or multiple linear regression that is to know the influence of both independent variables, either partially or simultaneously, to the dependent variable. Sampling was conducted randomly from 112 respondents. Data were analyzed by using simple linear regression statistic analysis and multiple linear analysis. The results showed that: 1) there was a positive and significant impact of Family Conflicts on the Learning Results of Social Studies students of class V with a correlation coefficient of 0.787 or contributing influence of 78.7% and partial test of 0.887. 2) There is a positive and significant effect of Learning Motivation to IPS Grade Students Learning Results with the level of correlation coefficient of 0.490 or contributing influence of 49% and partial test results of 0.700. 3) There is a positive and significant influence of Family Conflicts and Motivation Learning together to IPS Learning Outcomes with R = 0.802 or influence of 80.2%. Based on the above results it can be concluded the whole results of this analysis support the proposed hypothesis. The variable that has the greatest influence from the data calculation is the Family Conflict variable.